IMPLEMENTASI KONSEP MUROBBI DALAM BIMBINGAN KONSELING SANTRI DI PONDOK PESANTREN DARUL AMANAH BEDONO JAMBU KABUPATEN SEMARANG - Mustafidin, Ahmad; Andi, Andi Wahyudi; Ambari, M. Zaki; Ma’fudin, Alif (Transpublika Publisher, 2024)
Recently, the education system has transformed with the integration of Islamic boarding schools and formal education, known as the modern Islamic boarding school education system. Each institution has its own issues, but they prioritize Quran memorization, foreign languages, leadership, management, teaching materials, parenting, local culture, and religion. This study aims to examine the Murobbi superior program at Darul Amanah Bedono Islamic Boarding School in Semarang Regency. Quoting from Abdul Rahman's essay entitled